2021
DOI: 10.3390/v13081648
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seroprevalence Structure of the Russian Population during the COVID-19 Pandemic

Abstract: The SARS-CoV-2 pandemic, which came to Russia in March 2020, is accompanied by morbidity level changes and can be tracked using serological monitoring of a representative population sample from Federal Districts (FDs) and individual regions. In a longitudinal cohort study conducted in 26 model regions of Russia, distributed across all FDs, we investigated the distribution and cumulative proportions of individuals with antibodies (Abs) to the SARS-CoV-2 nucleocapsid antigen (Ag), in the period from June to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 71 publications
2
23
0
1
Order By: Relevance
“…From a practical point of view, epidemiological analysis of the state of collective immunity using serological methods (for determining the prevalence of SARS-CoV-2 Abs) and other epidemiological analysis approaches are more appropriate [ 12 , 13 ]. This article continues our previous publications analyzing SARS-CoV-2 Ab seroprevalence, such as our cross-sectional study of herd immunity in the St. Petersburg population [ 14 ] conducted in the early period of COVID-19 incidence (13–20 June 2020), as well as longitudinal seromonitoring of the population in 26 regions of Russia [ 15 , 16 , 17 , 18 , 19 , 20 ]. Features of seroprevalence in Belarus and Kyrgyzstan (2020–21) were also analyzed [ 21 , 22 ].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…From a practical point of view, epidemiological analysis of the state of collective immunity using serological methods (for determining the prevalence of SARS-CoV-2 Abs) and other epidemiological analysis approaches are more appropriate [ 12 , 13 ]. This article continues our previous publications analyzing SARS-CoV-2 Ab seroprevalence, such as our cross-sectional study of herd immunity in the St. Petersburg population [ 14 ] conducted in the early period of COVID-19 incidence (13–20 June 2020), as well as longitudinal seromonitoring of the population in 26 regions of Russia [ 15 , 16 , 17 , 18 , 19 , 20 ]. Features of seroprevalence in Belarus and Kyrgyzstan (2020–21) were also analyzed [ 21 , 22 ].…”
Section: Introductionsupporting
confidence: 65%
“…Previously, features of coronavirus infection and seroprevalence development dynamics (anti-SARS-CoV-2 Abs) in the Russian population in 2020 were characterized [ 1 , 15 , 16 ]. As mentioned above, the epidemic proceeded in St. Petersburg in the form of two waves (May and December 2020), of which the second was significantly higher ( p > 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is manifested as a high proportion of convalescents, although it is worth noting that a noticeable morbidity did not lead to the activation of transmission or the appearance of a significant number of contact persons. The age structure of seroprevalence, in contrast to a number of Russian regions [10,11,13,41], was characterized by a statistically significant increase in the indicator among persons in older age groups (50-70+ years; p < 0.0001) (Table 3). When quantifying Abs SARS-CoV-2 Nc, it was shown that: the minimum Ab levels (100 to 750 U/ml) prevailed among volunteers in the age groups 1-17 and 18-29 years old; and the maximum levels (751 to 3000+ U/ml) were identified among persons aged 50 to 70+ years.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a seroprevalence study that used sera collected between 28 September and 30 December 2020, in the Chelyabinsk region of the Russian Federation, showed that the crude prevalence of anti-SARS-CoV-2 Spike IgM was 3.2% [ 14 ]. Another seroprevalence study performed on the population of 26 regions of the Russian Federation identified that 17.8% of individuals had IgG antibodies to SARS-CoV-2 [ 15 ]. Another seroprevalence study performed on the population of 26 regions of the Russian Federation identified that 17.8% of individuals had IgG antibodies to SARS-CoV-2 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%